Analysis of Online Gold Investment Interest on E-Commerce: A Fiqh Muamalah Perspective: A Case Study of Housewives in Medan - Muhammad Rizky Lubis; Tuti Anggraini; Nurul Jannah (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
Online gold investment through e-commerce platforms is gaining popularity, particularly among housewives. This study analyzes their interest in online gold investment through the lens of Fiqh Muamalah, focusing on housewives in Medan City. Using qualitative methods, including interviews and document analysis, the research identifies economic, social, and religious factors that influence investment interest. Economic factors include price stability, ease of access, and product variety, while social factors encompass lifestyle trends, education, and trust in e-commerce platforms. From a Fiqh Muamalah perspective, online gold investment is permissible, provided it adheres to Islamic principles, such as clear contracts, freedom of agreement, asset existence, accurate measurements, and the absence of riba (usury). The study concludes that housewives are motivated to invest in gold for saving, inflation protection, and portfolio diversification, despite awareness of price fluctuations. Social influences, government policies, and stable economic conditions further drive interest. A strong understanding of Shariah principles and the selection of secure platforms are essential for ensuring safe and compliant investments